Factors restricting the use of the locative preposition Yu in classical Chinese : a modeling of recursive partitioning - 林静夏 Lin, Jingxia (2015)
Different accounts (Fang 2000; Dong 2006; Xu 2006; Xu 2008; et al.) of the optional use of locative preposition yu (於/于) in classical Chinese have been proposed. Yet there is still no agreement. This project proposed a new account via a statistical modeling method known as “recursive partitioning” to identify all the relevant factors correlated to the optional use of yu proposed previously. It is found that yu tends to follow verbs with high transitivity, which is opposite to Dong (2006) and Xu (2006). The historical development of Chinese is found to be the second most significant constraint: yu is less frequently used especially after the time of Shuihu Quanzhuan. In addition, yu tends to occur with a following monosyllabic NP. Other factors such as focus, zhi (之)-nominalization and prosody are found statistically insignificant. The results of this paper will serve as a quantitative base for further research on the grammatical function of yu.